Simplified signs a manual sign-communication system for special populations. Volume 1, Principles, background, and application - Bonvillian, John D.; Dooley, Tracy T.; Lee, Nicole Kissane; Loncke, Filip T.; Nelson-Metlay, Val; Open Book Publishers (Open Book Publishers, 2020)
"Simplified Signs presents a system of manual sign communication intended for special populations who have had limited success mastering spoken or full sign languages. It is the culmination of over twenty years of research and development by the authors. The Simplified Sign System has been developed and tested for ease of sign comprehension, memorization, and formation by limiting the complexity of the motor skills required to form each sign, and by ensuring that each sign visually resembles the meaning it conveys. Volume 1 outlines the research underpinning and informing the project, and places the Simplified Sign System in a wider context of sign usage, historically and by different populations. Volume 2 presents the lexicon of signs, totalling approximately 1000 signs, each with a clear illustration and a written description of how the sign is formed, as well as a memory aid that connects the sign visually to the meaning that it conveys. While the Simplified Sign System originally was developed to meet the needs of persons with intellectual disabilities, cerebral palsy, autism, or aphasia, it may also assist the communication needs of a wider audience - such as healthcare professionals, aid workers, military personnel , travellers or parents, and children who have not yet mastered spoken language. The system also has been shown to enhance learning for individuals studying a foreign language. Lucid and comprehensive, this work constitutes a valuable resource that will enhance the communicative interactions of many different people, and will be of great interest to researchers and educators alike."--Publisher's website.
Contents -- Preface and Acknowledgments / John D. Bonvillian and William Boone Bonvillian -- Postscript -- 1. Introduction / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke ; Addressing Concerns about Sign-Communication ; Training and Teaching ; Special Populations ; The Simplified Sign System ; Goals, Clarifications, and Recommendations ; Other Potential Users of the Simplified Sign System ; Contents and Structure of the Two Volumes -- 2. Use of Manual Signs and Gestures by Hearing Persons: Historical Perspectives / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke ; The Origins of Language ; Signs as a Natural and Universal Form of Communication ; Gestural and Sign Use Cross-Culturally ; Sign Communication in North America ; Europeans in the New World and their Communicative Interactions through Signs ; Early European Gestural Communication ; Concluding Remarks -- 3. Deaf Persons and Sign Languages / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke ; Deaf Education and the Recognition of Sign Languages ; Sign Production ; Different Sign Languages and Obstacles to Sign Communication Worldwide ; Unique Aspects of Sign Languages ; Iconic Signs ; Sign Language Acquisition ; Concluding Remarks -- 4. Sign Communication in Persons with an Intellectual Disability or with Cerebral Palsy / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke ; An Early Study Intellectual Disability ; Cerebral Palsy ; Recommendations for Enhancing the Sign-Learning Environment ; Selecting Signs -- 5. Childhood Autism and Sign Communication / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke ; Childhood Autism ; Sign-Communication Training and Teaching ; Dispelling Myths ; Teaching Generalization and Spontaneous Communication Skills ; Motor and Imitation Abilities ; Other Non-Oral Approaches ; Evaluative Comments -- 6. Sign-Communication Intervention in Adults and Children with Aphasia / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke ; Introduction to Aphasia and Apraxia ; Sign-Communication Training Outcomes ; Sign Facilitation of Spoken Language ; Acquired Childhood Aphasia and Landau-Kleffner Syndrome ; Developmental Language Disorder and Childhood Apraxia of Speech ; Concluding Remarks -- 7. Use of Manual Signs and Gestures by Hearing Persons: Contemporary Perspectives / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke ; Teaching Signs to Hearing Infants of Hearing Parents ; Socioeconomic Intervention Programs and Language ; Attention-Deficit Hyperactivity Disorder (ADHD) in Academic Settings ; Using Manual Signs to Improve Reading Comprehension ; Facilitating Foreign Language Vocabulary Acquisition ; Learning to Sign May Positively Affect One's Cognitive Abilities ; Concluding Remarks -- 8. Development of the Simplified Sign System / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke ; Background Information ; Step One: Iconic Sign Selection ; Step Two: Sign Formation Modification ; Step Three: Testing of Simplified Signs with Undergraduate Students ; Step Four: Comparison Testing of Simplified Signs ; Step Five: Feedback from Users ; Step Six: Memory Aids ; Concluding Remarks -- 9. Application and Use of the Simplified Sign System with Persons with Disabilities / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke ; Approaches to Teaching the Simplified Sign System ; Guidelines for Using the Simplified Sign System ; Frequently Asked Questions ; Concluding Remarks -- Appendix A: Sign Language Dictionaries and Other Sources -- Appendix B: Handshapes / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke -- Appendix C: Palm, Finger, and Knuckle Orientation / John D. Bonvillian, Nicole Kissane Lee, Tracy T. Dooley and Filip T. Loncke ; Palm Orientation ; Finger/Knuckle Orientation -- Glossary -- References -- Author Biographies -- Name Index -- Subject Index -- About the publishing team.
Available through Open Book Publishers.
Includes bibliographical references (pages 435-553) and indexes.
Mode of access: World Wide Web.
Keywords: Sign language